Soy Glycinin Contains a Functional Inhibitory Sequence against Muscle-Atrophy-Associated Ubiquitin Ligase Cbl-b - Tomoki Abe; Shohei Kohno; Tomonari Yama; Arisa Ochi; Takuro Suto; Katsuya Hirasaka; Ayako Ohno; Shigetada Teshima-Kondo; Yuushi Okumura; Motoko Oarada; Inho Choi; Rie Mukai; et al. (International Journal of Endocrinology)
Background. Unloading stress induces skeletal muscle atrophy. We have reported that Cbl-b ubiquitin ligase is a master regulator of unloading-associated muscle atrophy. The present study was designed to elucidate whether dietary soy glycinin protein prevents denervation-mediated muscle atrophy, based on the presence of inhibitory peptides against Cbl-b ubiquitin ligase in soy glycinin protein. Methods. Mice were fed either 20% casein diet, 20% soy protein isolate diet, 10% glycinin diet containing 10% casein, or 20% glycinin diet. One week later, the right sciatic nerve was cut. The wet weight, cross sectional area (CSA), IGF-1 signaling, and atrogene expression in hindlimb muscles were examined at 1, 3, 3.5, or 4 days after denervation. Results. 20% soy glycinin diet significantly prevented denervation-induced decreases in muscle wet weight and myofiber CSA. Furthermore, dietary soy protein inhibited denervation-induced ubiquitination and degradation of IRS-1 in tibialis anterior muscle. Dietary soy glycinin partially suppressed the denervation-mediated expression of atrogenes, such as MAFbx/atrogin-1 and MuRF-1, through the protection of IGF-1 signaling estimated by phosphorylation of Akt-1. Conclusions. Soy glycinin contains a functional inhibitory sequence against muscle-atrophy-associated ubiquitin ligase Cbl-b. Dietary soy glycinin protein significantly prevented muscle atrophy after denervation in mice.